Panic and Pandemics. - Thomas, Deborah A. (American Anthropologist, 2020)
An introduction is presented in which the editor discusses articles within the issue on topics including the rise of computer hacking and the hackerspace networks, the impact of plastic on the sense of belonging and citizenship in Kenya, and the issue of human energy expenditure in anthropology.